2022
DOI: 10.1155/2022/9621423
|View full text |Cite|
|
Sign up to set email alerts
|

Experimental Investigation to Utilize Adsorption and Absorption Technique to Reduce CO2 Emissions in Diesel Engine Exhaust Using Amine Solutions

Abstract: Due to the increased demand for global transportation needs, a long-range diesel engine is considered an important prime mover to fulfill the transportation demand. The major problem addressed by the diesel engines is it liberates harmful emissions and it also increases global warming. CO2 is considered an important greenhouse gas and it has to be controlled by diesel engines. In this research, extensive experimental work is done to identify a suitable solution to control CO2 emissions. For five different mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 27 publications
1
36
0
Order By: Relevance
“…Alcohols and ethers are oxygenated fuels or fuel additives for diesel engines that are an alternative to traditional fuels. Experiments have demonstrated that oxygenated fuels, such as esters, ethers, and alcohols, have many prospects for boosting diesel engine performance and lowering harmful emissions. Methanol, ethanol, propanol, pentanol, and butanol, all obtained from fossil or renewable sources, are regularly added to diesel fuel, with a maximum alcohol level of 20%. Other alcohols have also been tested to produce other esters, such as ethyl, propyl, and butyl esters. Yesilyurt et al used a diesel engine to evaluate various mixtures of alcohol additives with biodiesel.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alcohols and ethers are oxygenated fuels or fuel additives for diesel engines that are an alternative to traditional fuels. Experiments have demonstrated that oxygenated fuels, such as esters, ethers, and alcohols, have many prospects for boosting diesel engine performance and lowering harmful emissions. Methanol, ethanol, propanol, pentanol, and butanol, all obtained from fossil or renewable sources, are regularly added to diesel fuel, with a maximum alcohol level of 20%. Other alcohols have also been tested to produce other esters, such as ethyl, propyl, and butyl esters. Yesilyurt et al used a diesel engine to evaluate various mixtures of alcohol additives with biodiesel.…”
Section: Introductionmentioning
confidence: 99%
“…The increased heating value of n -octanol (LHV = 37.5–38.4 MJ/kg vs ethanol (21.4–26.9 MJ/kg) and butanol (26.9–36.0 MJ/kg) for CI engines is another key property. Because of its low solubility in water (4.6 g/L), n -octanol has higher pipeline compatibility than ethanol (miscible) and n -butanol (*77 g/L). , El-Seesy et al investigated the effects of quaternary biodiesel/methanol/ n -octanol/DEE. The pure methanol/waste frying oil biodiesel mixes were stable at all temperatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HC concentration is lower because C. inophyllum oil contains more than 11% oxygen by weight, resulting in more complete combustion and fewer incomplete combustion particles, as confirmed by similar published research works. 39 , 49 , 50 C. inophyllum oil also has low stoichiometric requirement for air, resulting in more efficient combustion of the air–fuel mixture. In DF mode, the inclusion of producer gas in the combustion chamber increases the CO 2 content instead of fresh air, causing ignition delay when compared to diesel fuel.…”
Section: Resultsmentioning
confidence: 99%
“…Carbon is inversely proportional to the air-fuel mixture since when combustion occurs inside the cylinder if and only if there is a lean air-fuel mixture, the reaction generates carbon monoxide as a consequence of the lack of oxygen to react to carbon dioxide. In Figure 6 , the diesel produced higher CO emissions for all applied loads than mixtures [ 21 23 ]. It can be seen that emissions in all cases tend to increase when the load is greater.…”
Section: Resultsmentioning
confidence: 99%